ANALISIS DINAMIKA EKSPOR MINYAK NILAM INDONESIA KE AMERIKA SERIKAT - Pinjung Nawang Sari; Slamet Hartono (Agro Ekonomi, 2010)
This study to analyze the Indonesin patchouli oil export to the world main market (USA), beteen 1989-2009 oeriod by analyzing : (1) the export oerformance, (2) the export competitiveness, and (3) the factors influenced to Indonesian patchouly oil export demand to USA. The export performance was measured  by trend of export, Trae Specialization Index (ISP), and Market Penetration Index  (IPP); while the export competitives was measured by Revealed Comparative Advantage (RCA) and Acceleration Ration (AR) Index. This study shows that : (1) the export performance have worked well : (a) trend export was positive, (b) ISP was positive (maturity level), (c) average of IPP was the biggest (2) the export competitiveness was strong; (a) average of RCA was the biggest, (b) AR value approached to +1, the export acceleration worked well;  (3) the significant factors influenced were world and France patchouli oil export, international price, and distillation point price. In order to maintained the export performance and decrease the competitiveness, should be done as following ; (1) to maintained the continuity of prioduct by making a commodity area consentration, (2) to strove the cooperation and support between government and industrialist, (3) government anda industrialist actively giving consulting to farmers for anticipating the world market needs and conditions, (4) improving the product quality; (5)mto give extra attention at buyer needs and stocks.